Pregnancy, stress and coping techniques: a review - Amin, Fiza; Tali, Tavseef Ahmad; Shah, Sieqa; Ara, Rifat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pregnancy is a common time to experience stress. Stress during pregnancy might be brought on by changes in your daily routine and physical discomforts. Certain forms of stress might result in issues like premature birth and major health problems like high blood pressure. Find out about strategies to help you deal with some of the stress in your life, such as consulting a licensed mental health professional, your healthcare provider, or friends and family. Stress relief techniques include deep breathing, meditation, and relaxation techniques. Even while stress is more common and has negative effects on both the mother and the child, there is still a lack of study on specific stress during pregnancy and coping mechanisms to avoid those negative effects.